2007
DOI: 10.1007/s10875-007-9106-y
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical, Immunohematological, and Molecular Study of Iranian Patients with Severe Congenital Neutropenia

Abstract: Severe congenital neutropenia (SCN) is a rareE primary immunodeficiency disorder characterized by early onset recurrent infections in association with persistent severe agranulocytosis. To identify the clinical, immunohematological, and molecular characteristics of patients with SCN, 18 Iranian patients with the mean age of 8.8 +/- 5.8 years were investigated in this study. All of these patients experienced severe neutropenia; the mean of absolute neutrophil count was 281.4 +/- 137.7 cells/mm3. Bone marrow fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 25 publications
2
20
1
1
Order By: Relevance
“…In this report, we present a case with consistent neutropenia who was clinically diagnosed as SCN, but where molecular studies indicated a diagnosis of CD40LD. While hematological abnormalities usually occur in association with neutropenia in SCN patients [1, 2], eosinophilia and monocytosis were not documented in this case, which is similar to other SCN patients in Iran [5]. Although the patient did not have a decreased serum level of IgA, and his serum IgM level was also within the normal range, the diagnosis of CD40LD was confirmed by mutational analysis.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In this report, we present a case with consistent neutropenia who was clinically diagnosed as SCN, but where molecular studies indicated a diagnosis of CD40LD. While hematological abnormalities usually occur in association with neutropenia in SCN patients [1, 2], eosinophilia and monocytosis were not documented in this case, which is similar to other SCN patients in Iran [5]. Although the patient did not have a decreased serum level of IgA, and his serum IgM level was also within the normal range, the diagnosis of CD40LD was confirmed by mutational analysis.…”
Section: Discussionsupporting
confidence: 71%
“…Early diagnosis and appropriate management remain the keys to prevent such complications [5]. Due to advances in immunological and molecular diagnostic techniques, a definitive diagnosis of most primary immunodeficiency diseases can now be easily obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sık ve ağır enfeksiyon varlığında hastaların laboratuvar değerlendirilmesinde algoritmada hemogramın ilk basamak inceleme olduğu ve total beyaz kan hücresi sayısı yanısıra dağılıma da dikkat edilmesi gerektiği unutulmamalıdır. Periferik yaymada nötropeninin yanı sıra kompansatris monosit ve eozinofil sayısında artış ile birlikte tekrarlayan enfeksiyon atakları nedeniyle serum immunoglobulin düzeylerinde yükseklik AKN olgularında görülebilmektedir (1,5,11). Olgu 7'de de belirgin eosinofili ve tüm immünoglobulin izotiplerinde artış gözlenmiştir.…”
Section: Sonuçunclassified
“…SCN3 patients, who carry homozygous nonsense mutations that are common to both transcript variants 1 and 2 of the HAX1 gene, show neurological manifestations in addition to neutropenia [5,8]. So far, the nonsense mutations in the HAX1 gene have been described in SCN3 patients of German [11], Japanese [10], Turkish [8,11], Iranian [8,13], Swedish [4,5], Kurdish [5], Ashkenazi Jewish [14], and British [14] ethnicity. We have recently reported the only missense mutation, encoding for Phe141-Leu, in SCN3 patients from two unrelated Arab families [7].…”
Section: Introductionmentioning
confidence: 99%